TELAAH TERHADAP MAZHAB HUKUM KRITIS: KEMUNCULAN, PEMIKIRAN DAN KRITIK - Ade Arif Firmansyah (Legalita, 2022)
The emergence of the Critical legal studies movement (CLS) in the map of legal thought which mainly developed in America is interesting to study further from its historical aspect, content of thought and criticism of the thoughts of critical legal school figures. This paper with all its limitations will try to elaborate further and provide an analysis of CLS. The results of the analysis show that: First, the critical school of law emerged as a thought movement that provided a new alternative to legal realism which was considered unsatisfactory and still traditional. In general, CLS thinking is a response to positivistic liberal legal thought which is considered a failure. Second, the legacy of CLS thinking basically tries to package a theory that aims to counter established thinking, especially regarding the norms and standards that have been built-in in existing legal theory and practice, which tend to be taken for granted. ), namely legal norms and standards based on the premise of liberal legal justice teachings. Third, the criticisms that arise regarding CLS's theses and claims relate to the following matters: regarding its relation to realism, regarding the rejection of liberalism, regarding fundamental contradictions, regarding deconstruction, regarding indetermination and regarding the unity of law and politics.